Mitochondria-Targeted Curcumin: A Potent Antibacterial Agent against Methicillin-Resistant Staphylococcus aureus with a Possible Intracellular ROS Accumulation as the Mechanism of Action - Carmen-Ecaterina Leferman; Laura Stoica; Bogdan Alexandru Stoica; Alin Dumitru Ciubotaru; Aida Corina Badescu; Camelia-Margareta Bogdanici; Tiberiu Paul Neagu; Cristina-Mihaela Ghiciuc (MDPI AG, 2023)
Mitocurcumin (a triphenylphosphonium curcumin derivative) was previously reported as a selective antitumoral compound on different cellular lines, as well as a potent bactericidal candidate. In this study, the same compound showed strong antimicrobial efficacy against different strains of methicillin-resistant Staphylococcus aureus (MRSA). The minimum inhibitory concentration was identical for all tested strains (four strains of MRSA and one strain of methicillin-sensitive Staphylococcus aureus), suggesting a new mechanism of action compared with usual antibacterial agents. All tested strains showed a significant sensitivity in the low micromolar range for the curcumin-triphenylphosphonium derivative. This susceptibility was modulated by the menadione/glutathione addition (the addition of glutathione resulted in a significant increase in minimal inhibitory concentration from 1.95 to 3.9 uM, whereas adding menadione resulted in a decrease of 0.49 uM). The fluorescence microscopy showed a better intrabacterial accumulation for the new curcumin-triphenylphosphonium derivative compared with simple curcumin. The MitoTracker staining showed an accumulation of reactive oxygen species (ROS) for a S. pombe superoxide dismutase deleted model. All results suggest a new mechanism of action which is not influenced by the acquired resistance of MRSA. The most plausible mechanism is reactive oxygen species (ROS) overproduction after a massive intracellular accumulation of the curcumin-triphenylphosphonium derivative.